Expanding perspectives on the significance of mitophagy in cancer. (December 2017) - Drake, Lauren E.; Springer, Maya Z.; Poole, Logan P.; Kim, Casey J.; Macleod, Kay F.
Abstract: Mitophagy is a selective mode of autophagy in which mitochondria are specifically targeted for degradation at the autophagolysosome. Mitophagy is activated by stresses such as hypoxia, nutrient deprivation, DNA damage, inflammation and mitochondrial membrane depolarization and plays a role in maintaining mitochondrial integrity and function. Defects in mitophagy lead to mitochondrial dysfunction that can affect metabolic reprogramming in response to stress, alter cell fate determination and differentiation, which in turn affects disease incidence and etiology, including cancer. Here, we discuss how different mitophagy adaptors and modulators, including Parkin, BNIP3, BNIP3L, p62/SQSTM1 and OPTN, are regulated in response to physiological stresses and deregulated in cancers. Additionally, we explore how these different mitophagy control pathways coordinate with each other. Finally, we review new developments in understanding how mitophagy affects stemness, cell fate determination, inflammation and DNA damage responses that are relevant to understanding the role of mitophagy in cancer.